Perencanaan Konsep Green Ruang Terbuka Hijau (RTH) Pada Pemukiman Kumuh Di Kelurahan Mario Kota Makassar - Sumarni Hamid Aly; Muralia Hustim; Mary Selintung; rasdiana zakaria; Ibrahim Djamaluddin; Nur An-Nisa Putry (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
The increase in urban slum areas provokes the adaptation impact of the community towards the capability conflict and the need for shelter. Slums management by displacing residents often raises new problems that are equally complicated. Hence, another alternative treatment by maintaining household-scale green open space (RTH) to improve the quality of life of the community and the environment is necessary. The problem of slums in big cities, including in the city of Makassar has not been able to be overcome properly, one of which is the problem of slums in the Mario Sub-District, Mariso District, Makassar City where the conditions of the slums are a severe result. The concept of managing the existing slums is not only producing buildings that are habitable, but also providing green open space is one of the solutions in structuring the existing area. At present, green open space not only provides open space planted with green vegetation but has the concept of Sustainable Open Green Space or known as the Green RTH concept. In this case, the concept introduced to local residents is green open where available wastewater treatment, composter and infiltration wells and biopores. It is these facilities which are expected to be able to deal directly with the problems of clean air, wastewater and waste problems that are always present in slums. The presence of the “Sustainable” Green Open Space which explains the concept of Green RTH namely green waste and green water can minimize the slums in the region. In green waste concept, 3 communal composters are made, each composter has a volume of 440 liters for 1235.775 liters / day of waste generation, while in the green water concept, a Wastewater Treatment Plant has an area of ​​302.8 m2, 1 infiltration well , 5 biopori infiltration holes and 2 hydrants.